The building of the Great Pyramid - Hynson, Colin (Columbus, OH : School Specialty Pub., 2006)
Presents an account of the building of Egypt's Great Pyramid, in graphic novel form, and includes background on ancient Egypt and the life of a pharaoh.
Includes index.
3.4
3-6
Keywords: Great Pyramid (Egypt) -- Comic books, strips, etc. -- Juvenile literature; Pyramids -- Egypt -- Design and construction -- Comic books, strips, etc. -- Juvenile literature; Great Pyramid (Egypt) -- Cartoons and comics; Pyramids -- Cartoons and comics; Cartoons and comics; Pyramids -- Egypt -- Comic books, strips, etc; Comic books, strips, etc